FINANCIAL PERFORMANCE AND FIRM VALUE: ON INDUSTRY BANKING - Hariyanto, Wiwit; Ningdiyah , Endra Wahyu; Abidin , Fityan Izza Noor (PT. Antis International Publisher, 2024)
Purpose: This research aims to find out The Influence of Leverage, Liquidity, and Company Size on Company Value with Financial Performance as an Intervening Variable Methodology/approach: This research uses methods quantitative with secondary data as a data source . In this research, the population data used are all companies banking conventional listed on the Indonesian Stock Exchange . Period observations made _ from 2018-2021 period . In this research, the non-probability sampling technique used in this research is Purposive Sampling. There are 11 companies banking conventional yeah used sample in this study. The data analysis technique used in this research is Structural Equation Modeling Partial Least Square (SEM-PLS). Findings: The results of this study show that Leverage has an Effect On Company Value, Liquidity Influential Regarding Company Value, Company Size Has an Influence On Company Value, Leverage Has an Influence On Financial Performance, Liquidity Influential Regarding Financial Performance, Company Size Has an Influence On Financial Performance, Financial Performance Has an Influence Towards Company Value. Financial Performance Mediates The Effect of Leverage on Company Value. Financial Performance Mediates Influence Liquidity Towards Company Value. Financial Performance Mediates Influence Company Size Against Company Value . Practical implications: The results of this research can be used as consideration for management, investors and interested parties in making investment decisions and policies so that they can produce optimal investment. Originality/value: this research connects between financial ratios with mark company through financial performance in banking industry companies . Previous research has not found connection in the banking industry in Indonesia.